1992
DOI: 10.1016/1044-0305(92)87089-h
|View full text |Cite
|
Sign up to set email alerts
|

Identification of deoxynucleoside—polyaromatic hydrocarbon adducts by capillary zone electrophoresis—Continuous Flow-fast atom bombardment mass spectrometry

Abstract: Capillary zone electrophoresis coupled to continuous flow-fast atom bombardment mass spectrometry is shown to have utility for the detection and characterization of adducts formed by the covalent attachment of four polyaromatic hydrocarbon (PAH) and amino-PAH compounds to deoxyguanosine. Normal scanning provided structural information for a 1.3 ng injection of a model adduct, while 1.3 ng of each of a mixture of adducts was sufficient to determine their molecular weights by monitoring the constant neutral loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…In one of the earliest examples, characterization of a mixture of several deoxynucleoside adducts of different polycyclic aromatic hydrocarbons by CZE-CF-FAB-MS was demonstrated by Wolf et al [74]. The adducts were formed by covalent attachment of four PAH and amino-PAH compounds to 2'-deoxyguanosine (dG).…”
Section: Dna Adductsmentioning
confidence: 98%
See 1 more Smart Citation
“…In one of the earliest examples, characterization of a mixture of several deoxynucleoside adducts of different polycyclic aromatic hydrocarbons by CZE-CF-FAB-MS was demonstrated by Wolf et al [74]. The adducts were formed by covalent attachment of four PAH and amino-PAH compounds to 2'-deoxyguanosine (dG).…”
Section: Dna Adductsmentioning
confidence: 98%
“…Therefore, separation of the modified and the unmodified nucleotides as well as within the modified nucleotide group offers the method the much needed selectivity. Nowadays, capillary LC, nano-LC [68][69][70][71][72][73], and CZE [57,[59][60][61][74][75][76][77][78][79][80][81][82][83][84][85][86][87] are more and more used as separation techniques for the analysis of DNA adducts and have proven to allow a very sensitive analysis procedure, e.g., in conjunction with mass spectrometric detection. In the elucidation of DNA adducts, ESI is currently the most used ionization technique when interfacing LC or CZE separations to MS.…”
Section: Dna Adductsmentioning
confidence: 99%
“…The authors concluded that, even though the adduct levels that can be detected with CE-MS are still several orders of magnitude higher than with the standard 32P-post-labeling technique, the possibility of identification justifies its parallel use. The group of Vouros [166] successfully analyzed PAH and amino-PAH adducts to deoxyguanosine by CE-FAB-MS. They could easily detect as low as 63 pg of synthetic PAH-DNA adduct by monitoring the signals arising from the loss of deoxyribose from the MH+ ion.…”
Section: Nucleotidesmentioning
confidence: 99%
“…The CE-CF-FAB systems reported in literature have all been based on either the liquid-junction (Minard et al, 1988;Reinhoud et al, 1989Reinhoud et al, , 1990Wolf et al, 1992) or the sheathflow design (Caprioli et al, 1989;Moseley, Deterding, & Tomer, 1989a,b;Moseley et al, 1990Moseley et al, , 1991Wolf & Vouros, 1995). The feasibility of CE-CF-FAB-MS was first reported by Minard et al (1988) with a liquid-junction interface.…”
Section: B Cf-fabmentioning
confidence: 99%
“…Initial liquid-junction interfaces were found to result in significant band-broadening and plate numbers were often limited to 10,000 theoretical plates (Minard et al, 1988;Reinhoud et al, 1989). Modification of the interface design by Caprioli et al (1989) and Wolf et al (1992) led to significant improvements in CE separation efficiency.…”
Section: B Cf-fabmentioning
confidence: 99%